EVALUATION OF THE EFFECTIVENESS OF USING THE PORTABLE SATELLITE COMMUNICATION COMPLEX IN HARD-TO-REACH AREAS - Chezhimbayeva, К.С.; Mukhamejanova, A.Д.; Kadirbayeva, Г.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
In the modern conditions of providing communications to remote and hard-to-reach areas, satellite systems that provide reliable and high-quality communications regardless of the terrain and infrastructure limitations are of particular relevance. The purpose of the study is to assess the effectiveness of using the PSK-400 satellite complex to organize communications in hard-to-reach areas. The key technical characteristics of the PSK-400 are analyzed, including throughput, coverage area, resistance to interference and signal delay. Scenarios for its use in various conditions are considered: providing communications in mountainous areas, arctic territories, remote industrial facilities and emergency zones. The effectiveness is assessed based on a comparative analysis with alternative solutions, as well as the results of practical testing. The advantages and possible limitations of using the PSC-400 are identified, including economic and operational aspects. The study is aimed at identifying the advantages, limitations and prospects for using this complex in various conditions. The obtained results confirm the feasibility of using the PSK-400 satellite complex for organizing communications in hard-to-reach areas, which can contribute to the development of digital infrastructure and increase the level of information accessibility in remote regions.